Euro-American influences on contemporary Malaysian metal sculptures from 1960 to 2010 - Zainuddin Abindinhazir@Abd. Rashid (2018)
Western Influences in Contemporary Malaysian Sculpture is an issue that is often dealt with throughthe ages. However, there has never been any scientific study undertaken in regard to thehistorical development of sculpture in Malaysia. Recognizing this neglect, the study wasconducted to document the influence of the West in the fabrication of local sculpture.However, the focus is strictly on sculptures that are made of metal from the 1960s tothe year 2010. The objective of this study, aims to explicate the style, form, iconography, andcontent. This connection involves questions of influence, culture, similarities, distinctions,identities and manifestations of local sculptors. In order to make this study a reality,researcher has combined the theory of Iconology by Erwin Panofsky and the concept of knowledgeby al-Imam al-Ghazzali. The study was conducted using the three stages of analysis(pre-iconographical description, analysis, and iconological interpretation) where theapproach of Islamic understanding is taken into account. Findings conclude that theearlier artists were vulnerable to Western influences in terms of form, style, and technique. Comparatively, more recent sculptors are more influenced interms of style and technique. In addition, factors of iconography and content were localized,triggered by cultural situations, issues, and goals. Discovered there as well, the concept of influences was short-lived and was not focused on any specific Western artist byeach individual of the local artists. There are no works which indicate dependencies inmaintaining the same form of their works afterward. It was seen as an entity that isinconsistent and changeable depending on different situations. The resulting works can also bebuilt from the combination of the influence of several Western artists. The study alsoshowed that artists are more affected when they start working from an early stage, and developedhis talent on the experience factor. The study also showed that the pioneer artists aremore influenced, especially in the construction of their early work. Factors ofexperience and skills upgrade later developed their talent. In all characteristics ofindependent variables, involving style, form and meaning have assimilated the local andWestern traditions, making Malaysia as a platform of integration. Artists of all racesconsider the uniformity of form and style, which tends toward Islamic values in their sculptural works as manifestations of cultural integration. This situation alsorealizes the continuation of national political policies. These findings are significant as avisual verification by image comparisons.